Mathematical Model of New Type of Train Buffer Made of Polymer Absorber—Determination of Dynamic Impact Curve for Different Temperatures - Mickoski, Hristijan; Mickoski, Ivan; Djidrov, Marjan; Zdraveski, Filip (My University, 2018)
Previous experimental knowledge has confirmed that one of the most influential factors affecting the performance of polymer friction absorbers embedded in buffer housing as part of the buffer and chain coupler is the temperature. This paper defines a mathematical model of a friction-type polymer absorber, PMKP-110. The presented mathematical model specifically includes the influence of the environment temperature on the dynamic impact curve for −60 °C and 15 °C. The dependence between the initial pre-tension of the buffer and the ambient temperature is calculated. The model involves an equation of motion for moving parts of the absorber, and the solution of the differential equation is achieved in Matlab. Results are given as diagrams of the impact deformation and impact speed of the polymer block, with assumed zero initial impact speed. The model can be used to analyze the action of the longitudinal forces that occur during transient conditions of the movement of the carriages.
Keywords: train buffers; polymer absorbers; temperature; impact force